Separation risk over union duration: An immediate itch? - Jalovaara Marika; Kulu Hill (Oxford University Press, 2025)
This study examines the risk of separation over union duration. Previous research reports a rising-falling pattern of divorce risk over marriage duration consistent with psychological notions of ‘honeymoon’ and ‘seven-year itch’. Little is known about the variation of the separation risk over cohabitation duration or over marriage duration when the length of partnership is measured from the beginning of coresidence. We include data on non-marital and marital unions and propose a novel way of treating cohabitation and marriage as episodes of the same union. We use Finnish large-scale register data and control for individuals’ observed and unobserved characteristics. Our results show that in cohabitations, the separation rate is highest at the beginning of union. Entry into marriage is followed by a significant drop in separation levels and a modest rising-falling pattern, which is independent of the length of pre-marital cohabitation. Marriage entails permanence, with a short ‘honeymoon’ effect and a long-term ‘effect’, much of which probably reflects self-selection of committed and satisfied cohabiters to marriage.